Endoloop technique for laparoscopic cornuectomy: A safe and effective approach for the treatment of interstitial pregnancy. Issue 8 (28th April 2016) - Faioli, Raffaele; Berretta, Roberto; Dall'Asta, Andrea; Di Serio, Maurizio; Galli, Letizia; Monica, Michela; Frusca, Tiziana
Abstract: Interstitial pregnancy (IP) occurs within the intramural portion of the tube and accounts for 2% of ectopic pregnancies. Surgery is considered the most definitive treatment for IPs, although there is no clear consensus regarding the optimal approach. In this paper we describe the advantages of cornual resection performed using the Endoloop technique and present three patients who were successfully treated using this approach. IP diagnosis was confirmed at two and three‐dimensional ultrasound and laparoscopy in all cases. Fertility sparing surgery with cornuectomy by Endoloop ligature technique demonstrated low mean operating time and blood loss, and allowed the quick recovery and discharge of all patients. Laparoscopy has become the gold standard surgical approach for IP. Cornual resection or excision is the most commonly performed procedure. In our case series, the Endoloop technique showed excellent treatment outcomes in terms of effectiveness, blood loss, operative time, recovery and post‐procedure fertility. Because of these features, Endoloop appears to be a suitable option for the laparoscopic management of IPs, both in elective and emergency settings.